The epidemiology of Shiga toxin-producing Escherichia coli infections in the South East of England: November 2013–March 2017 and significance for clinical and public health. Issue 6 (17th April 2019) - Carroll, Kevin J.; Harvey-Vince, Lisa; Jenkins, Claire; Mohan, Keerthi; Balasegaram, Sooria
Abstract : Purpose. This study describes the epidemiology of Shiga toxin-producing Escherichia coli (STEC) infections in a population in the South East of England. Methods. From 1 November 2013 to 31 March 2017 participating diagnostic laboratories reported Shiga toxin gene ( stx ) positive real-time PCR results to local public health teams. Stx positive faecal samples/isolates were referred to the Gastrointestinal Bacteria Reference Unit (GBRU) for confirmation by culture and typing by whole genome sequencing (WGS). Key clinical information was collected by public health teams. Results/Key findings. Altogether, 548 faecal specimens (420 were non-travel associated) were stx positive locally, 535 were submitted to the GBRU. STEC were isolated from 42 %, confirmed by stx PCR in 21 % and 37 % were PCR negative. The most common non-travel associated STEC serogroups were O157, O26, O146 and O91. The annualized incidence of confirmed STEC infections (PCR or culture) was 5.8 per 100 000. The ratio of O157 to non-O157 STEC serogroups was 1:7. The annualized incidence of non-O157 haemolytic uraemic syndrome-associated Escherichia coli (HUSEC) strains was 0.4 per 100 000. Bloody diarrhoea was reported by 58 % of cases infected with E. coli O157, 33 % of cases infected with non-O157 HUSEC strains and 12 % of other lower risk non-O157 strains. Overall, 76 % of non-O157 HUSEC isolates possessed the eae virulence gene. Conclusions. HUSEC including serogroup O157 were uncommon and more likely to cause bloody diarrhoea than other STEC. The routine use of s tx PCR testing can influence clinical management. Understanding the local epidemiology facilitates a proportionate public health response to STEC, based on clinical and microbiological characteristics including stx subtype(s).